Altered spontaneous brain activity in patients with comitant exotropia before and after surgery: A resting-state fMRI study. (September 2022) - Wu, Qian; Guo, Wei; Hu, Hao; Li, Rui; Zhu, Hui; Chen, Xiang-Xun; Xu, Xiao-Quan; Liu, Hu; Wu, Fei-Yun
Abstract: Patients with comitant exotropia (CE) would usually develop compromised binocular vision and impaired stereoscopic depth perception, which could result in a profound decrease in quality of life. Although the deviated optic axis could be corrected surgically, the impaired stereovision and sensory eye balance may sometimes remain remnant. This study was to investigate the brain functional alterations in patients with CE before and after surgery, using resting-state functional magnetic resonance imaging (fMRI) with amplitude of low-frequency fluctuation (ALFF). Thirty-five patients with CE were recruited to undergo a preoperative fMRI scan, as well as 24 healthy controls (HCs). Twenty-four of the patients were available for rescanned fMRI one month after surgery. The ALFF method was used to evaluate the group differences of spontaneous brain activity. The correlations between ALFF values and clinical variables were analyzed in the patient group. Preoperatively, compared with HCs, 35 patients with CE showed significantly decreased ALFF values in one cluster involving bilateral calcarine sulcus, lingual gyrus and cuneus. The ALFF values in the above cluster were negatively correlated with disease duration (r = −0.379, P = 0.033). One month after surgery, 24 patients with available rescanned fMRI demonstrated increased ALFF values in one cluster located in bilateral cuneus, calcarine sulcus and lingual gyrus relative to the preoperative collection, while still reduced ALFF values in the cluster involving left calcarine sulcus and lingual gyrus compared with HCs. Our study revealed the functional changes of patients with CE in visual-associated brain areas before and after surgery. The findings may provide a new perspective for understanding the underlying pathological mechanisms of CE. Highlights: Identify the decreased brain functional activity in patients with comitant exotropia. The brain functional activity partially restored one month after surgery. Provide an available method for discerning the treatment response for patients with comitant exotropia.